What's Gaby cooking : Grilling all the things : 100+ recipes to make you an absolute pro - Dalkin, Gaby, 1986- (Abrams, 2024)
A healthy grilling book for every kind of griller--from first-timers to seasoned pros to anyone who just wants to cook outside more--from New York Times bestselling author Gaby Dalkin. If you've ever been intimidated by the idea of grilling, Gaby Dalkin is here to help you conquer your fears and become a backyard pro. From the perfect steak to cedar-plank fish to pizza and fruits and veggies and everything in between, Dalkin reveals her secrets for marinating, spicing, and grilling anything you can think of. And of course, she'll talk grill mechanics: the difference between grills (gas and charcoal), smokers, pizza ovens, and the cooking techniques that go along with each, so readers are prepared to choose the best equipment for any recipe and get started. With 100 recipes to cover every part of the meal, including appetizers, seafood, meat and poultry, vegetables, and desserts, there will be super-quick high-heat recipes to get dinner on the table ASAP and more low and slow "project" recipes that take some time and work well for weekend parties. In traditional Dalkin fashion, there will be menus, timelines, and hosting tips to really set the mood.